Donations, risk attitudes and time preferences: A study on altruism in primary school children - Silvia Angerer; Daniela Glätzle-Rützler; Philipp Lergetporer; Matthias Sutter (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2014)
We study with a sample of 1,070 primary school children, aged seven to eleven years,how altruism in a donation experiment is related to children's risk attitudes and intertemporalchoices. Examining such a relationship is motivated by theories of reciprocalaltruism that provide a cornerstone to understand human social behavior. We find thathigher risk tolerance and patience in intertemporal choice increase, in general, the levelof donations, albeit the effects are non-linear. We confirm earlier results that altruismincreases with age during childhood and that girls are more altruistic than boys. Havingolder brothers makes subjects less altruistic.
Keywords: C91; D03; D63; D64; 330; Altruism; risk attitudes; intertemporal choices; experiment; children